IMPROVEMENT OF LEGAL, MANAGEMENT AND FINANCIAL ASPECTS ON “SUKSES BERSAMA” BUMDES IN PEJATEN VILLAGE, KRAMATWATU DISTRICT, SERANG REGENCY - Asnawi Asnawi; Encep Saefullah; Ina Khadijah (Yayasan Education and Social Center, 2022)
Partners in the Stimulus Community Partnership Program (PKMS) are the Pejaten Village Government and the manager of the Village-Owned Enterprises (BUMDes)